2023
DOI: 10.3389/fpsyt.2023.1103572
|View full text |Cite
|
Sign up to set email alerts
|

Causing trouble and being transmissible: COVID-19 survivors’ experiences of stigma and discrimination in South Korea

Abstract: BackgroundThe stigma associated with coronavirus disease (COVID-19) is relatively neglected in policies for handling the disease. Stigmatization occurs only within specific social contexts in local societies.ObjectiveThis study aims to examine COVID-19 survivors’ experiences of social stigma and discrimination in South Korea in the first 2 years of the pandemic.MethodsSemi-structured interviews were conducted.ResultsOf 52 participants, 45 reported that they had to cope with stigma and discrimination in their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…As a result, they were exposed to violence, discrimination and racism (62). Studies suggest an increase in stigmatization and xenophobia worldwide since the onset of the COVID-19 pandemic (63,64). In line with the findings of this study, others have indicated that MIMs are at an additional risk of being blamed for the spread of the SARS-CoV-2 virus (30).…”
Section: Discussionsupporting
confidence: 80%
“…As a result, they were exposed to violence, discrimination and racism (62). Studies suggest an increase in stigmatization and xenophobia worldwide since the onset of the COVID-19 pandemic (63,64). In line with the findings of this study, others have indicated that MIMs are at an additional risk of being blamed for the spread of the SARS-CoV-2 virus (30).…”
Section: Discussionsupporting
confidence: 80%
“…Lessons learned from previous epidemics such as Middle East respiratory syndrome coronavirus (MERS-CoV), HIV, and Ebola show that stigma tends to persist during and after the epidemic [19][20][21]. Various media reports document that people suspected of having COVID-19 have been kicked out of their rental apartments and removed from their workplaces, especially after completing the mandatory quarantine [22]. When the participants were asked whether they agreed with the statement "People do not want to work in the same room with someone who has contracted COVID-19 and recovered", 60.2% of the participants in the first group and 10.3% in the second group agreed.…”
Section: Discussionmentioning
confidence: 99%